2020
DOI: 10.1071/ah19225
|View full text |Cite
|
Sign up to set email alerts
|

Allied health primary contact services: results of a 2-year follow-up study of clinical effectiveness, safety, wait times and impact on medical specialist out-patient waitlists

Abstract: ObjectiveLong specialist out-patient waitlists are common in public health facilities, but not all patients require consultation with a medical specialist. Studies of single allied health primary contact services have shown they provide timely, appropriate care and reduce demand on medical specialist out-patient waitlists. This study evaluated the collective benefits across multiple allied health primary contact services and models to determine their clinical effectiveness, safety, timeliness of care and impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Our findings demonstrate a gain in technical efficiency and reveal an opportunity to screen a greater number of patients. Consultant-led clinic appointments previously allocated to screening for an OPG in patients with NF1 can now be utilised by other patients, reducing delays between appointments (Stute et al 2021). The benefits of surveillance and screening clinics in facilitating earlier detection of pathology while simultaneously reducing the costs associated is well understood (Watts et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate a gain in technical efficiency and reveal an opportunity to screen a greater number of patients. Consultant-led clinic appointments previously allocated to screening for an OPG in patients with NF1 can now be utilised by other patients, reducing delays between appointments (Stute et al 2021). The benefits of surveillance and screening clinics in facilitating earlier detection of pathology while simultaneously reducing the costs associated is well understood (Watts et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Over the last decade, there has been a growing interest in the development of physiotherapy-led models of care; in these models, the physiotherapist conducts the initial appointment, with the objective of reducing unnecessary appointments with the ENT specialist. [15][16][17][18][19] In the UK, Kasbekar et al 16 and Burrows et al 17 demonstrated the effectiveness of physiotherapy-based models of care, where 22 per cent and 3 per cent of patients, respectively, avoided the need to see an ENT specialist.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the multidisciplinary team (MDT) primary contact approach on ENT specialist review waitlist times was further improved when speech pathology and audiology were also included. Stute et al 15 and Távora-Vieira et al 20 demonstrated that speech pathology and audiology services can reduce the need to see an ENT specialist. Barnes 18 further confirmed the benefits of this MDT approach, reporting that ultimately only 10 per cent of patients required a consultation with an ENT specialist or neurologist for vestibular symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have found that breastfeeding training for physicians and nurses is inadequate, 4–6 lacks clarity regarding the optimal educational approach, 7 and many healthcare professionals default to their own experiences of breastfeeding 8–10 . Moreover, training for staff such as those working in dietetics and speech and language therapy, who often support medically complex feeding, is patchy and may be formula industry‐funded 11–16 …”
Section: Introductionmentioning
confidence: 99%